Constitutional laws in the Visegrad countries - Попович, Наталия Васильевна (Problems of legality, 2016)
The article is devoted to investigation of the place of constitutional laws in the system of constitutional legislation of association of four Central European countries: Poland, Hungary, the Slovak Republic and the Czech Republic; to study the nature and functional use of constitutional laws, their specific characteristics and varieties, clarifying features, including special procedures for adoption and amendment of constitutional law and place in the legislation. The current system of sources of law in Visegrad Group was formed under the influence of Roman, Austrian (Germanic), Socialist (Soviet) Law in the course of historical development, now it is identified as a system of civil law, which is changing and evolving under the influence of European international legal standards and values (laws of the European Union), formed primarily within the civil law. In the countries of the Visegrad Four constitutional laws are the integral part of the constitutional system. Thus, in countries of Visegrad Group functional use of constitutional laws is different (amending; implementation of international agreements; regulation of certain matters provided by the constitution, etc.). It is also mentioned in the article that in Poland, the term «constitutional law» after adoption of the Constitution of 1997 is not applied officially in terms of legislation, though, at the same time some lawyers and politicians use the term in their publications and speeches, collectively interpreting the notion of constitutional law as the law that is first and utmost connected with the content of the Constitution, with amendments to the Constitution, and the adoption of the new Constitution. It is noted that «constitutional laws» can be understood not only as the laws that amend or supplement the Constitution but also as the laws the Constitution refers to or necessity of which is directly provided by the current Constitution. These laws specify certain provisions of the Constitution, are adopted by the legislature or a referendum in a specific order.